2019
DOI: 10.1097/phm.0000000000001042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Twitch Contraction Induced by Magnetic Stimulation on Expression of Skeletal Muscle Fibrosis Related Genes and Limited Range of Motion in Rats

Abstract: Objective We examined the effects of twitch contraction induced by lumbar spinal root magnetic stimulation on immobilization-induced limited range of motion and skeletal muscle fibrosis in rat soleus muscle. Design The groups included male Wistar rats (controls), rats with both bilateral ankle joints immobilized with plaster casts for 4 wks (immobilization [IM]), and rats in which twitch contraction of the soleus muscle was induced by lumbar magnetic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In contrast, an experimental study in rats that were immobilized in a shortened position showed that although magnetic stimulation prevented fibrosis, it did not stop muscle atrophy [19]. TMS depolarizes almost all the spinal motor neurons that innervate the target muscle in healthy individuals [27] and also has a transsynaptic effect [28].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, an experimental study in rats that were immobilized in a shortened position showed that although magnetic stimulation prevented fibrosis, it did not stop muscle atrophy [19]. TMS depolarizes almost all the spinal motor neurons that innervate the target muscle in healthy individuals [27] and also has a transsynaptic effect [28].…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, it was recently reported that neuromuscular magnetic stimulation produces a clinical improvement in muscle strength by counteracting the muscle atrophy present in amyotrophic lateral sclerosis [17] and in the paretic limb atrophy in patients with cerebrovascular accident [18]. Furthermore, lumbar spinal root magnetic stimulation also prevented fibrosis in rats immobilized in a shortened muscle position [19].…”
Section: Introductionmentioning
confidence: 99%